Animal sciences, Volume 1 - Cobb, Allan B (National Academy of Sciences, 2012)
In response to the popularity and critical acclaim of its other full-color science sets for students, Macmillan Reference USA has developed a comprehensive series of colorful, informative sets in the sciences. The Macmillan Science Library for Students will engage students at many levels -- from middle school and high school -- to nonmajors in college and lay readers in public libraries. This new series offers the most comprehensive views of key areas in the world of science. Each set explores all facets of the topic, offering not only descriptive and analytical information, but also cultural and ethical issues, and career opportunities in many fields of science. Geared to high school and undergraduate levels, this color-illustrated reference has the strength of interdisciplinarity: coverage encompasses animal development, behavior, ecology, and issues (animal testing, rights, habitat loss, etc.). In the entry on animal testing, Ian Quigley (U. of Texas, Austin) stands firmly on middle ground: some experimentation necessary, much of it not, and things are getting better. In "Habitat Loss," Elliot Richmond (Austin Community College) discusses species-endangering anthropogenic causes: agriculture, urbanization, grazing, deforestation, mining, water projects, fire suppression, recreation, and traffic in non-native species. Features include a comprehensive glossary at the end of each volume, specific glossaries in the margins of each entry, and a comprehensive list of entries in 24 categories (e.g. animal groups, cell biology, historical figures in science, and humans and the animal world). In-depth indexes appear in each volume. Of the 25 contributors, 16 hail from institutions in Austin, Texas, while the rest are based elsewhere in the U.S. Annotation c. Book News, Inc., Portland, OR (booknews.com)